2019
DOI: 10.1007/s00009-019-1319-9
|View full text |Cite
|
Sign up to set email alerts
|

On the Third-Order Jacobsthal and Third-Order Jacobsthal–Lucas Sequences and Their Matrix Representations

Abstract: In this paper, we first give new generalizations for third-order Jacobsthal {J (3) n } n∈N and third-order Jacobsthal-Lucas {j (3) n } n∈N sequences for Jacobsthal and Jacobsthal-Lucas numbers. Considering these sequences, we define the matrix sequences which have elements of {J (3) n } n∈N and {j (3) n } n∈N . Then we investigate their properties.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…There have been many studies on the generalized Tribonacci numbers V n (x, y, z; a, b, c). For more information, please refer to [3,9,30,31,33,34] and closely related references therein. Some special cases of the generalized Tribonacci sequence V n (x, y, z; a, b, c) are as follows:…”
Section: Motivationsmentioning
confidence: 99%
“…There have been many studies on the generalized Tribonacci numbers V n (x, y, z; a, b, c). For more information, please refer to [3,9,30,31,33,34] and closely related references therein. Some special cases of the generalized Tribonacci sequence V n (x, y, z; a, b, c) are as follows:…”
Section: Motivationsmentioning
confidence: 99%
“…In [6], the authors provided many basic identities for third-order Jacobsthal numbers, {J (3) n } n≥0 , and third-order Jacobsthal-Lucas numbers, {j (3) n } n≥0 (see also [5] and reference therein):…”
Section: Basic Propertiesmentioning
confidence: 99%
“…It is well-known that the Jacobsthal sequence (sequence A001045 in [5]) {Jn} is defined recursively by the equation, for n ≥ 0 Jn+2 = Jn+1 + 2Jn in which J0 = 0 and J1 = 1. Then Jacobsthal sequence (second order Jacobsthal sequence) is 0, 1, 1, 3,5,11,21,43,85,171,341,683,1365,2731, 5461, 10923, ... This sequence has been studied by many authors and more detail can be found in the extensive literature dedicated to these sequences, see for example, [6,7,8,9,10,11,12,13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%